2009
DOI: 10.5488/cmp.12.3.411
|View full text |Cite
|
Sign up to set email alerts
|

High-order coupled cluster method calculations of spontaneous symmetry breaking in the spin-half one-dimensional J_{1}-J_{2} model

Abstract: In this article we present new formalism for high-order coupled cluster method (CCM) calculations for "generalized" ground-state expectation values and the excited states of quantum magnetic systems with spin quantum number s 1 2. We use high-order CCM to demonstrate spontaneous symmetry breaking in the spin-half J 1 -J 2 model for the linear chain using the coupled cluster method (CCM). We show that we are able to reproduce exactly the dimerized ground (ket) state at the Majumdar-Ghosh point (J 2 /J 1 = 1 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 43 publications
(111 reference statements)
2
10
0
Order By: Relevance
“…4. Similar to previous research [25], we found that the results for the extrapolation of LSUBn data are not accurate in the region where c1 α α ≈ . So, the spin gap obtained from CCM is not displayed in Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…4. Similar to previous research [25], we found that the results for the extrapolation of LSUBn data are not accurate in the region where c1 α α ≈ . So, the spin gap obtained from CCM is not displayed in Fig.…”
Section: Resultssupporting
confidence: 85%
“…In Refs. [24,25], it was shown that CCM can be used to analyze the dimer and plaquette valence-bond phases of quantum spin systems perfectly. Here, we also apply CCM to the study of the dimerized state of the sawtooth chain.…”
Section: Introductionmentioning
confidence: 99%
“…The LSUBn approximation becomes exact for n → ∞, and so we can improve our results by extrapolating the "raw" LSUBn data to n → ∞. There are well-tested extrapolation rules [15,19,20,46,47,[51][52][53][54][56][57][58][59][60] for the ground-state energy per spin e GS = E GS (n)/N, the magnetic order parameter m s (n), and the spin gap ∆ e (n). We use e GS (n) = a 0 + a 1 (1/n) 2 + a 2 (1/n) 4 for the ground-state energy, m s (n) = b 0 + b 1 (1/n) 1/2 + b 2 (1/n) 3/2 for the magnetic order parameter, and ∆ e (n) = c 0 + c 1 (1/n) + c 2 (1/n) 2 for the spin gap.…”
Section: Introductionmentioning
confidence: 96%
“…It was found in Refs. [46] and [47] that the opening of the spin gap at the transition point to the valence-bond phase is well described by the CCM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation